Antifungal Properties of Bioactive Compounds Isolated from Fucus vesiculosus Supercritical Carbon Dioxide Extract - Katarzyna Tyśkiewicz; Felix Rüttler; Renata Tyśkiewicz; Artur Nowak; Marcin Gruba; Anita Wziątek; Agnieszka Dębczak; Michał Sandomierski; Walter Vetter (Molecules)
The exploration of natural antifungal substances from algal origins is significant due to the increasing resistance of pathogens to conventional antifungal agents and the growing consumer demand for natural products. This manuscript represents the inaugural investigation into the antifungal attributes of bioactive compounds extracted from Fucus vesiculosus via supercritical carbon dioxide (scCO2) extraction utilizing contemporary countercurrent chromatography (CCC). In aligning with the prospective utilization of this extract within the agricultural sector, this study also serves as the preliminary report demonstrating the capability of Fucus vesiculosus scCO2 extract to enhance the activity of plant resistance enzymes. The fractions obtained through CCC were subjected to evaluation for their efficacy in inhibiting the macrospores of Fusarium culmorum. The CCC methodology facilitated the successful separation of fatty acids (reaching up to 82.0 wt.% in a given fraction) and fucosterol (attaining up to 79.4 wt.% in another fraction). All CCC fractions at the concentration of 1.0% were found to inhibit 100% of Fusarium culmorum growth. Moreover, Fucus vesiculosus scCO2 extract was able to activate plant resistance enzymes (Catalase, Ascorbic Peroxidase, Guaiacol Peroxidase, Phenylalanine Ammonia-Lyase, and Phenylalanine Ammonia-Lyase Activity).